Factores asociados a mortalidad temprana en pacientes que inician hemodiálisis en el Hospital Regional de Loreto 2016 - 2021 - Montes de Oca Luna, Marilia Nair (2023)
Chronic kidney disease (CKD) represents a major epidemiological, economic, social, global and regional problem. More than 2.5 million people receive renal replacement therapy or hemodialysis, and it is estimated that this number is increasing; the main causes of CKD are diabetes mellitus and arterial hypertension, in addition to other diseases that trigger and exacerbate its development. In Loreto, only a small percentage of patients with CKD are admitted to renal replacement therapy (hemodialysis). It has been seen that mortality in patients who start renal replacement therapy is higher during the first 90 days, which is defined as early mortality in hemodialysis. Some factors associated with early mortality in hemodialysis have been identified, such as socio-demographic factors, primary cause of renal disease, vascular access, laboratory factors, and associated comorbidities. The present study aims to determine the risk factors associated with early mortality in patients who start hemodialysis in the Regional Hospital of Loreto. It will be analytical, observational, multivariate, ambispective. Including those patients older than 18 years, affiliated to the SIS, who enter from January 2016 to December 2021 to the hemodialysis program, or who have required emergency hemodialysis and subsequently enter the hemodialysis program, who have received at least three sessions of renal replacement therapy at the Regional Hospital of Loreto.